Lumped parameter modelling in femoral popliteal artery for normal and severe conditions - Kaha, Asrizan; Taib, Ishkrizat; Paisal, Muhammad Sufyan Amir; Tajul Arifin, Ahmad Mubarak; Ismail, Al Emran; Asmuin, Norzelawati; Abdul Haq, Reazul Haq; Chatpun, Surapong; Yamamoto, Takahisa; Osman, Kahar (Penerbit UTHM, 2018)
Development of numerical technique would be benefited to diagnose the biological structure especially in femoropopliteal artery. Blood circulatory system and heart hemodynamic performance can be simulated by applying lumped parameter method. Thus, this study aims to develop numerical modelling in femoropopliteal artery by constructing an electric analog model to the system. Three different cases have been considered in this study; normal blood condition, aneurysm and atherosclerosis conditions. Normal blood condition is also analysed as a basis study of comparison between aneurysm and atherosclerosis conditions. The electrical analog model with 3 nodes and terminal load at the end of this model are proposed. This algorithm is then verified against numerical data simulated using commercial software. The study shows that normal and abnormal conditions effect instantaneously to pressure and flow waveforms. The result shows that the highest peak pressure is shown in atherosclerosis condition about 3.2×105 Pa as compared to normal and aneurysm conditions which obtained about 1.7×104 Pa and 0.1×104 Pa, respectively. On the other hand, the flow resistance increase about 16 fold as the radius in aneurysm at 3.0 mm is reduced to 1.4 mm for the aneurysm condition. Therefore, the aneurysm condition in the second segment shows the highest flow rate about 3.0×10-3m3/s as compared to the other conditions. In conclusion, the obtained waveform propagation from the linear analysis of the lumped parameter modelling shows that the periodic mean pressures and flow rate distributions in large arteries are highly depend on the resistances and the compliances. The quantitative variations of blood pressure and flow waveforms along the arterial of femoral popliteal artery from this model followed clinical trends as the normal condition show a stable pressure and flow rate obtained compare to the atherosclerosis and aneurysm condition.